AKUNTABILITAS PELAYANAN PUBLIK DI KELURAHAN MAHAKERET TIMUR KECAMATAN WENANG KOTA MANADO - PANDEY, STELA; LENGKONG, FLORENCE; RURU, JOORIE (Sam Ratulangi University, 2019)
the purpose of this study was to determine the accountability of public services in the East MahakeretVillage, Wenang District, Manado City. This study used a descriptive-qualitative approach. Public serviceaccountability is seen from three aspects, namely financial accountability, benefit or effectiveness accountability,and procedural accountability. The research informants were the lurah, head of the public service section andgovernment staff / implementers of the East Mahakeret village and several community members. Data collectionuses interview guidelines, while the analysis technique used is the analysis of interactive models from Miles andHubernann. The results showed: (1) 1. Financial accountability in public services in the East Mahakerat Districtwas good because financial planning of the implementation of public service programs / activities was stipulatedin the SKPD work plan for the Kelurahan Government, and budget realization for public service deliveryactivities in each fiscal year was made / compiled in the Government Agency Performance Accountability Report(LAKIP) which is informed and accessible to the public. (2) Benefit Accountability or Effectiveness in the PublicServices in East Mahakeret Village is good because the type of public service that is held is public services whichare the scope of authority of the kelurahan government, and policies taken / implemented for the implementationof public services according to the authority and the interests of the community. (3) Procedural Accountability inpublic services in the East Mahakeret Village is good because the implementation of services already has aStandard Operating Procedure or SOP that is appropriate to the type of service, clear, uncomplicated, concise,and easy to implement by officers / village officials, and is followed by the people served.Keywords: Accountability, Public Services, Kelurahan.